2001
DOI: 10.1016/s0020-7292(01)00480-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adherence and immune response in recurrent urinary tract infection

Abstract: This study showed that increased receptivity of vaginal epithelial cells to pathogens and lower local immunity may play an important role in the pathogenesis of recurrent UTI in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
4
17
0
2
Order By: Relevance
“…It may confirm a significant role of this virulence factor among bacterial strains responsible for pyelonephritis. Results of research conducted by Sunman et al (2001) and Raksha et al (2003) also showed hydrophobic nature of the cell surface of E . coli isolated from patients with UTIs.…”
Section: Discussionmentioning
confidence: 79%
“…It may confirm a significant role of this virulence factor among bacterial strains responsible for pyelonephritis. Results of research conducted by Sunman et al (2001) and Raksha et al (2003) also showed hydrophobic nature of the cell surface of E . coli isolated from patients with UTIs.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, greater number of the E. coli strains demonstrated hydrophobicity. Previous studies on urinary tract infection cases reported high rate of exhibition of cell surface hydrophobicity by some pathogenic strains of E. coli (Sunman et al, 2001;Raksha et al, 2003). The presence of hydrophobic strains of E. coli in this water sources is an indication that the water could be a potential source of agents of urinary tract infections or gastroenteritis if consumed.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with the results of previous studies. 6,13 The high hydrophobicity of the bacterial cell surface promotes their adherence to various surfaces like mucosal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%